2010
DOI: 10.1063/1.3422475
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation phenomena in two-dimensional piecewise smooth discontinuous maps

Abstract: In recent years the theory of border collision bifurcations has been developed for piecewise smooth maps that are continuous across the border, and has been successfully applied to explain nonsmooth bifurcation phenomena in physical systems. However, many switching dynamical systems have been found to yield two-dimensional piecewise smooth maps that are discontinuous across the border. The theory for understanding the bifurcation phenomena in such systems is not available yet. In this paper we present the firs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Beyond its relation with homoclinic bifurcations for flows, such type of bifurcation scenarios have been observed in more applied contexts modeled by both one and n-dimensional piecewise-smooth maps. Examples of such applications where these bifurcation scenarios appear are power electronics ( [45,29,113,67,136,7,85,134]), control theory ( [46,58,51,133,135,50,51]), economics ( [126]) or neuroscience ( [57,74,84,89,103,122,116,124,125,123]). Typically, these bifurcation scenarios are numerically observed in two-dimensional parameter spaces near codimension-two bifurcation points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond its relation with homoclinic bifurcations for flows, such type of bifurcation scenarios have been observed in more applied contexts modeled by both one and n-dimensional piecewise-smooth maps. Examples of such applications where these bifurcation scenarios appear are power electronics ( [45,29,113,67,136,7,85,134]), control theory ( [46,58,51,133,135,50,51]), economics ( [126]) or neuroscience ( [57,74,84,89,103,122,116,124,125,123]). Typically, these bifurcation scenarios are numerically observed in two-dimensional parameter spaces near codimension-two bifurcation points.…”
Section: Introductionmentioning
confidence: 99%
“…Often, due to the complexity of real applications, one-dimensional maps are not enough and one needs to consider maps in higher dimensions. Examples of two (or higher)-dimensional piecewise-smooth maps are found as Poincaré (or stroboscopic) maps in non-autonomous mechanical systems ( [37,109,44]), but their are also found in power electronics ( [45,29,113,67,136,7]), control theory ( [46,133,135,51]) or mathematical-neuroscience or biology ( [124,125,57,103,123,116]). Piecewise-smooth maps in higher dimensions are also obtained when studying Filippov flows in R n (n ≥ 3) ( [49]); they appear as half-return Poincaré maps, and become discontinuous close to grazing and Hopf bifurcations ( [56,108,94,111,39,38]).…”
Section: Introductionmentioning
confidence: 99%
“…4, from which two critical observations can be made: (a) there is a sudden transition from a period-1 orbit to period-11 orbit and (b) after this first bifurcation takes place, there is a sequence of bifurcations where the periodicity increases or decreases by 1. As it will be shown later, these peculiar bifurcation phenomena are caused by the fact that the Poincaré map of the system is discontinuous [Jain & Banerjee, 2003;Rakshit et al, 2010].…”
Section: System Descriptionmentioning
confidence: 97%
“…Such maps also have been used to model induction motor drives with Direct Torque Control [Suto et al, 2009]. In all cases one-dimensional (1D) (or at most two-dimensional (2D)) discontinuous maps sufficed in describing the system dynamics with reasonable accuracy, and the theory for such maps is available [Jain & Banerjee, 2003;Rakshit et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…As the work by Rakshit et al [16] demonstrated a property of the normal form map that the unstable manifolds fold at every intersection with the x-axis, and the image of every fold point is a fold point. The stable manifolds fold at every intersection with the y-axis and the preimage of every fold point is a fold point.…”
Section: Fixed Points and Their Classificationmentioning
confidence: 99%